OʻZBEKISTON RESPUBLIKASIDA KONSTITUTSIYAVIYLIK VA QONUN USTUVORLIGI: NAZARIY VA AMALIY JIHATLAR (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article analyzes the legal nature of the principles of constitutionalism and the rule of law in the Republic of Uzbekistan, their significance within the system of public administration, and the mechanisms for ensuring their implementation. The supremacy of the Constitution as the highest legal authority, the system of normative legal acts, the independence of the judiciary, and the process of building a rule-of-law state are examined from a scientific perspective. The article also highlights the role of constitutional values in a modern democratic society.